Designing a macroprudential capital buffer for climate-related risks - Florian Bartsch; Iulia Busies; Tina Emambakhsh; Michael Grill; Mathieu Simoens; Martina Spaggiari; Fabio Tamburrini (European Central Bank (ECB), 2024)
Amid the growing financial vulnerabilities posed by climate change, we investigate macroprudential capital buffers to mitigate systemic risks and increase the resilience of the banking sector. Leveraging granular data and state-of-the-art stress testing methods, we quantify potential bank losses attributed to climate-related transition risks. Focusing on short-term transition scenarios, we document a significant variance among banks in their risk exposure, with the most exposed institutions being those characterized by lower excess capital. Subsequently, we introduce a methodological framework for tailoring bank-specific buffer requirements to cover these losses, offering macroprudential authorities a practical method for calibrating climate-related macroprudential capital buffers, complementing microprudential policies. While we focus our application on transition risks, the framework can be extended to capture all climate risks in general. The study demonstrates the potential of macroprudential capital buffers to mitigate potential climate-related losses and contributes to the understanding of the appropriate prudential policy response to these challenges.
Keywords: E61; G21; G28; Q54; 330; macroprudential policy; climate change; transition risk; climate risk